Digital marketing model on Hospitality business’s social media : (Study at Indoluxe Hotel Jogjakarta) - Carla Puspita, Fabiola; Prayudi, Prayudi; Arief Sosiawan, Edwi (Universitas Ahmad Dahlan, 2024)
The increasing growth of hotels from year to year has resulted in increasingly tight competition in the hotel business in Yogyakarta. In order to win competitive business competition, Indoluxe Hotel Jogjakarta carries out digital marketing through social media in its promotional activities. Social media in the current digital era has no doubt about its existence and has an important role in building relationships between hotels and customers. The aim of this research is to find a digital marketing model on Indoluxe Hotel Jogjakarta social media. The method used in this research uses a qualitative approach by collecting data through interviews, documents and analysis on Indoluxe Hotel Jogjakarta social media. The object of this research is Indoluxe Hotel Jogjakarta's social media with the research subject being the sales & marketing department which manages Indoluxe Hotel Jogjakarta's social media. Overall, digital marketing on social media that has been carried out by Indoluxe Hotel Jogjakarta has implemented the right steps. This can be seen from the results of analysis and evaluation using Forrester's 5I model so that hotels can find out whether the social media they run has an impact on business or vice versa. The results of this research found a digital marketing model on Indoluxe Hotel Jogjakarta social media by dividing the model into three aspects, namely planning, action and involvement. Planning phase to build brand, product and service awareness. The action phase is the stage where the brand, in this case the Indoluxe Hotel Jogjakarta, can interact with customers. Lastly, namely engagement where Indoluxe Hotel Jogjakarta maintains relationships to create customer loyalty.